2018
DOI: 10.1021/acs.iecr.8b02243
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Andrographolide from Andrographis paniculata Dried Leaves Using Supercritical CO2 and Ethanol Mixture

Abstract: The increase in the number of world's elderly population and changes in their lifestyle has triggered to the formation of diseases susceptible communities. Inherent with the aforementioned conditions, the need in andrographolide as one of natural remedies isolated from the leaves of Andrographis paniculata also increases. In this work, supercritical fluid extraction employing CO 2 −ethanol mixture as solvent has shown its capability in extracting andrographolide from dried leaves of A. paniculata. The androgra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Andrographolide, 1 (Figure ), a labdane diterpenoid, is isolated from Andrographis paniculata . Compound 1 had a variety of medicinal properties such as antiviral, anti-inflammatory, , antioxidant, , and antitumor activities. , More recently, Ghosh et al reported that the andrographolide–gold nanoparticle hybrid could ameliorate viper venom-induced toxicities .…”
Section: Introductionmentioning
confidence: 99%
“…Andrographolide, 1 (Figure ), a labdane diterpenoid, is isolated from Andrographis paniculata . Compound 1 had a variety of medicinal properties such as antiviral, anti-inflammatory, , antioxidant, , and antitumor activities. , More recently, Ghosh et al reported that the andrographolide–gold nanoparticle hybrid could ameliorate viper venom-induced toxicities .…”
Section: Introductionmentioning
confidence: 99%
“…Ethanol cosolvent is commonly used in supercritical fluid extractions because it is regarded to be a safe solvent. 74 Figure 8 shows a relationship of the extracted yield of selected andrographolide components 6 with predicted π* values of scCO 2 −EtOH mixtures. The extracted yields (Figure 8) tended to have a linear increase with the π* values.…”
Section: Applications Of the Predictive Framework To Separation Proce...mentioning
confidence: 67%
“…Extraction yield (wt %) of andrographolide from Andrographis paniculata dried leaves using supercritical CO 2 and ethanol cosolvent mixture varying ethanol (EtOH) composition (up to 12.5 mol %) as a function of Kamlet–Taft dipolarity/polarizability (π*) of mixtures at a constant temperature of 40 °C, pressure of 10 MPa, extraction time of 7 h. Symbol lists: solid red circle = 0 mol % EtOH (pure CO 2 ), blue solid triangle up = 5 mol % EtOH, solid yellow tilted square = 7.5 mol % EtOH, (orange solid hexagon) = 10 mol % EtOH, and aqua blue solid star = 12.5 mol % EtOH. Data for the extraction are taken from ref . The π* values were calculated by the framework and correction functions of fluorescence (eqs and and Table S9).…”
Section: Applications Of the Predictive Framework To Separation Proce...mentioning
confidence: 99%
See 2 more Smart Citations